2017
DOI: 10.1080/19390211.2017.1310781
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Oral Supplementation With Ovoderm on Human Skin Physiology: Two Pilot Studies

Abstract: Collagens and hyaluronic acid have long been used in pharmaceuticals and food supplements for the improvement of skin elasticity and hydration. These compounds provide the building blocks of the skin. Ovoderm is an oral supplement obtained from eggshells that contains naturally occurring collagen and glycosaminoglycans, such as hyaluronic acid. We evaluated the efficacy of Ovoderm on skin biophysical parameters related to cutaneous aging such as elasticity, hydration, and pigmentation. Two pilot studies were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…We found that the oral supplementation with the Study Product had a positive impact on fine lines, wrinkles, and skin tone, which are facets of overall skin appearance. These findings are supported by other oral nutrition intervention studies where similar bioactive ingredients or sources were utilized, and similar results or the basis (the architecture) for the current results were found . As the objective Canfield Visia‐CR™ system was utilized for skin analysis, we also employed the subjective modified FACE‐Q questionnaire as a means of capturing more robust information.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…We found that the oral supplementation with the Study Product had a positive impact on fine lines, wrinkles, and skin tone, which are facets of overall skin appearance. These findings are supported by other oral nutrition intervention studies where similar bioactive ingredients or sources were utilized, and similar results or the basis (the architecture) for the current results were found . As the objective Canfield Visia‐CR™ system was utilized for skin analysis, we also employed the subjective modified FACE‐Q questionnaire as a means of capturing more robust information.…”
Section: Discussionsupporting
confidence: 86%
“…These findings are supported by other oral nutrition intervention studies where similar bioactive ingredients or sources were utilized, and similar results or the basis (the architecture) for the current results were found. [10][11][12]15,22,23 As the objective Canfield Visia-CR™ system was utilized for skin analysis, we also employed the subjective modified FACE-Q questionnaire as a means of capturing more robust information. The results on the subjective questionnaire in part support the objective improvements in overall skin appearance as observed with a reduction in crow's feet by week 4; however, the potential for placebo response cannot be discounted, as there were also aspects of the study that were not different between the groups.…”
Section: Con Clus Ionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eggshell membrane has been shown in vitro to be an ingredient that increases the cellular activity, collagen production and reduces the damage caused by UV light [16,17,23]. So far, few studies have been performed to investigate the effect of orally administered eggshell membrane on various skin parameters [24]. To our knowledge, this is the first clinical study set out to explore the efficacy of Ovoderm®, eggshell membrane, on skin physiology and appearance related to cutaneous aging.…”
Section: Discussionmentioning
confidence: 97%